2000
DOI: 10.1046/j.1525-1497.2000.91139.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, controlled trial of an interactive videodisc decision aid for patients with ischemic heart disease

Abstract: OBJECTIVE:To determine the effect of the Ischemic Heart Disease Shared Decision-Making Program (IHD SDP) an interactive videodisc designed to assist patients in the decisionmaking process involving treatment choices for ischemic heart disease, on patient decision-making. DESIGN:Randomized, controlled trial. SETTING:The Toronto Hospital, University of Toronto, Toronto, Ontario, Canada. PARTICIPANTS:Two hundred forty ambulatory patients with ischemic heart disease amenable to elective revascularization and ongoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 22 publications
6
119
0
1
Order By: Relevance
“…For example, all 9 trials evaluating knowledge have shown that decision aids significantly improve patient knowledge, with a weighted mean difference of 19% (compared with 16% in this trial). 8,[12][13][14][15][16][17][18][19][20] Similarly, all 6 of the trials that examined decisional conflict reported statistically significant improvements with decision aids of magnitudes virtually identical to our results. 17,18,[21][22][23][24] However, decision aids have had variable impacts on management in the 3 tri- als evaluating medical therapies: one 24 reported a 76% increase in hepatitis B vaccination with a decision aid, another 25 reported a nonsignificant 8% reduction in hormone replacement use, and the third 17 reported a nonsignificant 6% increase in ASA use among patients with NVAF at low risk of stroke.…”
Section: Discussionsupporting
confidence: 81%
“…For example, all 9 trials evaluating knowledge have shown that decision aids significantly improve patient knowledge, with a weighted mean difference of 19% (compared with 16% in this trial). 8,[12][13][14][15][16][17][18][19][20] Similarly, all 6 of the trials that examined decisional conflict reported statistically significant improvements with decision aids of magnitudes virtually identical to our results. 17,18,[21][22][23][24] However, decision aids have had variable impacts on management in the 3 tri- als evaluating medical therapies: one 24 reported a 76% increase in hepatitis B vaccination with a decision aid, another 25 reported a nonsignificant 8% reduction in hormone replacement use, and the third 17 reported a nonsignificant 6% increase in ASA use among patients with NVAF at low risk of stroke.…”
Section: Discussionsupporting
confidence: 81%
“…There have been few randomised controlled trials examining the effectiveness of online access and services on improving health outcomes, [47][48][49] but some work has been undertaken focusing on the impact of new technologies in relation to patient decision making and health outcomes. [50][51][52][53] Like all systematic reviews, evidence was gathered from various resources from a specific time period and, as such, there may be several new studies recently published that have not been included in this review.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Standardized (simulated) patient actors portraying informed decision-making scenarios have been developed to train surgeons, 15 but such training may be no more effective than traditional lectures. 16 Other methods targeted at pa tients, such as decision aids, 17 counselling, 18 interactive videodiscs 19 or audiotapes of visits, 20 may improve the decision-making process.…”
Section: Limitationsmentioning
confidence: 99%